Epithelial-to-Mesenchymal Plasticity Harnesses Endocytic Circuitries - Corallino, Salvatore; Malabarba, Maria Grazia; Zobel, Martina; Di Fiore, Pier Paolo; Scita, Giorgio (Frontiers in Oncology, 2015)
The ability of cells to alter their phenotypic and morphological characteristics, known as cellular plasticity, is critical in normal embryonic development and adult tissue repair and contributes to the pathogenesis of diseases, such as organ fibrosis and cancer. The epithelial-to-mesenchymal transition (EMT) is a type of cellular plasticity. This transition involves genetic and epigenetic changes as well as alterations in protein expression and post-translational modifications. These changes result in reduced cell-cell adhesion, enhanced cell adhesion to the extracellular matrix, and altered organization of the cytoskeleton and of cell polarity. Among these modifications, loss of cell polarity represents the nearly invariable, distinguishing feature of EMT that frequently precedes the other traits or might even occur in their absence. EMT transforms cell morphology and physiology, and hence cell identity, from one typical of cells that form a tight barrier, like epithelial and endothelial cells, to one characterized by a highly motile mesenchymal phenotype. Time-resolved proteomic and phosphoproteomic analyses of cells undergoing EMT recently identified thousands of changes in proteins involved in many cellular processes, including cell proliferation and motility, DNA repair, and – unexpectedly – membrane trafficking (1). These results have highlighted a picture of great complexity. First, the EMT transition is not an all-or-none response but rather a gradual process that develops over time. Second, EMT events are highly dynamic and frequently reversible, involving both cell-autonomous and non-autonomous mechanisms. The net results is that EMT generates populations of mixed cells, with partial or full phenotypes, possibly accounting (at least in part) for the physiological as well as pathological cellular heterogeneity of some tissues. Endocytic circuitries have emerged as complex connectivity infrastructures for numerous cellular networks required for the execution of different biological processes, with a primary role in the control of polarized functions. Thus, they may be relevant for controlling EMT or certain aspects of it. Here, by discussing a few paradigmatic cases, we will outline how endocytosis may be harnessed by the EMT process to promote dynamic changes in cellular identity, and to increase cellular flexibility and adaptation to micro-environmental cues, ultimately impacting on physiological and pathological processes, first and foremost cancer progression.